Inhibitory activity of leaf and bark extracts of the Tree Tetragastris panamensis (Engl.) Kuntze, on in vitro growth of Moniliopthora roreri (cif) H.C.Evans, Stalpers, Samson & Benny. (1978), Biology Laboratory, UNAN- MANAGUA, 2021 (Revista Torreón Universitario, 2022)
This research was carried out to evaluate the inhibitory activity of the extracts at different concentrations of bark and leaf of Tetragastris panamensis (Engl.) Kuntze on in vitro growth of Moniliopthora roreri (cif) H.C. Evans, Stalpers, Samson & Benny. ( 1978). The experiment consisted of three phases: first, the Soxhlet method was used to extract the oils by matrices and estimate their efficiency, then, a fungal susceptibility analysis was carried out where the method used was that of diffusion in agar Kirby-Bauer modifying it for the phytopathogen, finally, the minimum inhibitory concentration of the extracts of both matrices was determined using the serial dilution method,  for all these processes, the variables temperature, time and exposure to light were controlled. The result was analyzed from the application of mixed methods integrating both quantitative and qualitative approaches which allowed us to verify that both matrices have fungicidal action. However, bark oil has greater fungicidal activity compared to phytopathogen.Article derived from monographic thesis entitled: Inhibitory activity of leaf extracts and bark of the tree Tetragastris panamensis (Engl.) Kuntze, on in vitro growth of Moniliopthora roreri (cif) H.C.Evans, Stalpers, Samson & Benny. (1978), Biology laboratory, UNAN-MANAGUA, 2021. In the period from January to October 2021.
Keywords: Inhibitory activity; fungicidal action; minimum inhibitory concentration